O (des)enlace do interdiscurso, da cenografia e do ethos entre Meu nome é esperança! e Corações de pedra, de Ganymédes José - Deliberal, Sonia Maria (2019)
The present dissertation is located in the line of research entitled "Text and Discourse in Oral and Written Modalities", part of the Program of Postgraduate Studies in Portuguese Language, Pontifical Catholic University of São Paulo - PUC / SP. The central theme of this research is to analyze, from the perspective of the Discourse Analysis (AD) of the French line, the exclusion between two novels of Ganymédes José, namely: My Name is Hope!, 1974, and Hearts of Stone, The aim is to approach literature as a producer of discourse that is constituted in - and by - language; thus, it is necessary to observe the socio-historical conditions, in order to situate the discourses contemplated for analysis. The selected theme is justified by the observations made during the student environment, during a course in Basic Education, in contact with deaf students, at which time it was possible to verify the presence of exclusion. The research problem raised was to verify the way in which the writer positioned himself and constituted his discourses in the different contexts before the exclusions. Based on studies carried out by Maingueneau, the present investigation aims at the observation: of the role of interdiscourse in the consideration of the effects of sense and in the interweaving of different universes; of scenography, with the development of the enunciation constituted between the enunciator, co-enunciator, involving the topography and the chronography; and of ethos in the construction of the image of the enunciator accomplished by the co-enunciator and its process of incorporation. This study reveals the importance of theoretical and methodological procedures to favor the knowledge of discourse